Targeted Atrial Fibrillation Therapy and Risk Stratification Using Atrial Alternans - Neha Muthavarapu; Anmol Mohan; Sharanya Manga; Palak Sharma; Aditi Kishor Bhanushali; Ashima Yadav; Devanshi Narendra Damani; Pierre Jais; Richard D. Walton; Shivaram P. Arunachalam; Kanchan Kulkarni (Journal of Cardiovascular Development and Disease, 2023)
Atrial fibrillation (AF) is the most persistent arrhythmia today, with its prevalence increasing exponentially with the rising age of the population. Particularly at elevated heart rates, a functional abnormality known as cardiac alternans can occur prior to the onset of lethal arrhythmias. Cardiac alternans are a beat-to-beat oscillation of electrical activity and the force of cardiac muscle contraction. Extensive evidence has demonstrated that microvolt T-wave alternans can predict ventricular fibrillation vulnerability and the risk of sudden cardiac death. The majority of our knowledge of the mechanisms of alternans stems from studies of ventricular electrophysiology, although recent studies offer promising evidence of the potential of atrial alternans in predicting the risk of AF. Exciting preclinical and clinical studies have demonstrated a link between atrial alternans and the onset of atrial tachyarrhythmias. Here, we provide a comprehensive review of the clinical utility of atrial alternans in identifying the risk and guiding treatment of AF.